Remodeling the tumor immune microenvironment via siRNA therapy for precision cancer treatment - Lingxi Jiang; Yao Qi; Lei Yang; Yangbao Miao; Weiming Ren; Hongmei Liu; Yi Huang; Shan Huang; Shiyin Chen; Yi Shi; Lulu Cai (Elsevier, 2023)
How to effectively transform the pro-oncogenic tumor microenvironments (TME) surrounding a tumor into an anti-tumoral never fails to attract people to study. Small interfering RNA (siRNA) is considered one of the most noteworthy research directions that can regulate gene expression following a process known as RNA interference (RNAi). The research about siRNA delivery targeting tumor cells and TME has been on the rise in recent years. Using siRNA drugs to silence critical proteins in TME was one of the most efficient solutions. However, the manufacture of a siRNA delivery system faces three major obstacles, i.e., appropriate cargo protection, accurately targeted delivery, and site-specific cargo release. In the following review, we summarized the pharmacological actions of siRNA drugs in remolding TME. In addition, the delivery strategies of siRNA drugs and combination therapy with siRNA drugs to remodel TME are thoroughly discussed. In the meanwhile, the most recent advancements in the development of all clinically investigated and commercialized siRNA delivery technologies are also presented. Ultimately, we propose that nanoparticle drug delivery siRNA may be the future research focus of oncogene therapy. This summary offers a thorough analysis and roadmap for general readers working in the field.